A study of corrosion protection efficiency of silica nanoparticles acrylic coated on mild steel electrode. (March 2019) - Rajkumar, R.; Vedhi, C.
Abstract: Silica nanoparticles (SNPs) were synthesized using rice husk by eco-friendly method. The physico-chemical characterization of SNPs was investigated by Fourier Transform Infrared Spectroscopy (FT-IR), X-ray diffraction (XRD), Scanning electron microscopy (SEM) and Energy Dispersive X-Ray Spectroscopy (EDS). FT-IR spectrum shows the main characteristic peak of SiOSi at 468 cm −1 indicating the formation of SNPs. The XRD pattern revealed the formation of crystalline SNPs and the particle grain size value were found to be 5 nm. The surface morphology was observed by SEM. EDS result showed that the composition of silicon and oxygen in SNPs is found to be 47.54% and 28.24%, respectively. Acrylic coating containing SNPs was directly coated on the mild steel surface and the anticorrosive behavior was examined by polarization curve and electrochemical impedance spectroscopy in 1% HCl and 3.5% NaCl solution. It was found that silica/acrylic coating showed better corrosion protection efficiency as compared to that of pure acrylic coating. Silica/acrylic coating acted as good anticorrosive behavior for 3.5% of NaCl solution. Highlights: Synthesis of silica nanoparticles by vacuum condition. It act as a excellent protective layer on mild steel electrode. Silica nanoparticles is prepared from agricultural waste.